2006
DOI: 10.1245/aso.2006.03.592
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy Before Neoadjuvant Chemotherapy for Determining Axillary Status and Treatment Prognosis in Locally Advanced Breast Cancer

Abstract: This study validates the prognostic stratification of patients with a complete pathologic axillary response to neoadjuvant chemotherapy. The addition of SLN biopsy to cN0 patients before treatment increased accurate nodal staging by 53%, eliminated completion axillary lymph node dissection in 15%, and demonstrated an improved prognosis in 28% of pCRAX patients. SLN biopsy before treatment provides accurate staging of cN0 patients; allows acquisition of standard treatment markers, prognostic biomarkers, and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 35 publications
0
31
0
3
Order By: Relevance
“…The pathologic complete response rate with neoadjuvant chemotherapy for patients with known positive axillary lymph node reported rages from 11 to 60% [16][17][18][19]. We observed that the subset of patients treated with DE presented a substantial gain in terms of axillary pCR when compared to the subset of patients treated with FEC.…”
Section: Discussionmentioning
confidence: 71%
“…The pathologic complete response rate with neoadjuvant chemotherapy for patients with known positive axillary lymph node reported rages from 11 to 60% [16][17][18][19]. We observed that the subset of patients treated with DE presented a substantial gain in terms of axillary pCR when compared to the subset of patients treated with FEC.…”
Section: Discussionmentioning
confidence: 71%
“…They found that occult metastases were found in 10% of patients with histologically negative axilla. A study by Cox et al 30 demonstrated that 27% of their patients had a complete pathologic axillary response, and these patients had a higher overall survival than patients with residual disease. Xing et al 31 conducted a meta-analysis of 21 studies that examined the results of SLN biopsy after chemotherapy.…”
Section: Role Of Slnb In Patients Undergoingmentioning
confidence: 99%
“…Contrary to the high number of studies reporting SLNB after NAC, only a few studies have reported the results of performing SLNB before NAC. [16][17][18][19][20][21][22][23] The candidates for SLNB in this setting were patients with large tumors and clinically negative nodes before NAC. Two studies demonstrated that SLNB can also provide accurate results in patients with large breast tumors not treated with chemotherapy.…”
Section: Sentinel Lymph Node Biopsy Before Neoadjuvant Chemotherapymentioning
confidence: 99%
“…SLNB is considered to be contraindicated for patients on NAC for several reasons; however, many studies have reported positive results of SLNB before and/or after NAC. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In this review article, we discuss the issues surrounding SLNB performed before or after NAC by reviewing the published literature and our experience, based on which we assess the optimal timing for SLNB in the NAC setting.…”
Section: Introductionmentioning
confidence: 99%